Analyzing Lexical Density and Readability of Reading Texts in English Textbook “Stop Bullying Now” by Mahrukh Bashir - Miskiyah, Nafkhatul; Amalia, Taranindya Zulhi (Institut Agama Islam Negeri Kudus, 2022)
The complexity of the text can be determined by lexical density and readability tests. Therefore, the purposes of this research are to find out the lexical density and readability of reading texts and the relevancy of them to the grade level of reading texts. This research took a descriptive qualitative method with library research. The subject is taken from the eleven reading texts in the English textbook